Assessment of the influence on left ventricle by potassium oxonate and hypoxanthine–induced chronic hyperuricemia. Issue 2 (January 2023) - Lin, Cuiting; Zheng, Qiang; Li, Yongmei; Wu, Ting; Luo, Jian; Jiang, Yanqing; Huang, Qinghua; Yan, Caixin; Zhang, Leqi; Zhang, Wei; Liao, Hui; Yang, Yang; et al.
Cellular cytoplasmic xanthine oxidase (XO)–mediated uric acid synthesis and extracellular excess uric acid exposure are both causes of cardiomyocytic injury under the condition of hyperuricemia (HUA). Potassium oxonate suppresses uric acid degradation to increase extracellular concentration, while hypoxanthine is the catalytic substrate of XO. We aimed to observe cardiac damage in a chronic HUA mouse model induced by potassium oxonate and hypoxanthine. The mouse model was established by the co-administration of potassium oxonate and hypoxanthine for eight weeks. Then, left ventricular parameters were examined by echocardiographic evaluation, and the heart tissues were harvested for further histopathological analysis. The results showed that plasma uric acid was persistently elevated in the model mice, which demonstrated the stable establishment of chronic HUA. The left ventricular anterior wall was significantly thickened in the model group compared with the blank control group. After the end of modeling, the left ventricular anterior wall thickness of the hyperuricemic mice increased compared with that of blank group. The histological analysis showed and myocardial structure disorganization in the model group compared with the blank control. The above cardiac impairment changes could be attenuated by allopurinol pretreatment. This study systematically assessed cardiac damage in a chronic HUA mouse model. In addition, it provides useful information for future HUA-associated heart injury mechanism investigation and therapeutic treatment evaluation.